Suppressing lipid biosynthesis in Mycobacterium tuberculosis through polyketide synthase 13 thioesterase inhibition: Insights from computational analysis - Maha M. Alawi; Hattan S. Gattan; Azzah S. Alharbi; Mohammed H. Alruhaili; Ibrahim A. Al-Zahrani; Saad B.AL Masaud; Vivek Dhar Dwivedi; Esam I. Azhar (Journal of Infection and Public Health)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a global health challenge, particularly with the emergence of multidrug-resistant and extensively drug-resistant strains. Mycolic acid biosynthesis is essential for the integrity of Mtb's cell wall, offering promising therapeutic intervention targets. The thioesterase domain of polyketide synthase 13, Pks13-TE, is at the heart of this pathway and, therefore, an attractive drug target. Methods: 1228 natural compound libraries were computationally screened to identify the most potentially active Pks13-TE inhibitors. In silico virtual screening was done on top candidates using MTiOpenScreen based on binding affinity. The molecular dynamics simulation was applied to analyze the structural properties in terms of stability, compactness, and flexibility of the post-validation of the docking result. The MMGBSA method was used to calculate the binding-free energy. Further conformational landscape analysis was applied using FEL. Results: Three such promising compounds were identified: ZINC000008214766, ZINC000006845076, and ZINC000253498755. The compound ZINC000008214766 showed the most favorable binding interactions by making multiple hydrogen bonds and van der Waals contacts with Pks13-TE active site residues. MD simulations have revealed that it is consistently stable with minimal fluctuations and compact conformation. The MM/GBSA analysis confirmed its superior binding energetics compared to other candidates. The FEL analysis highlighted narrow and deep minima for ZINC000008214766, indicating strong conformational stability. Properties of ZINC000006845076 and ZINC000253498755 followed moderate binding but low stability. Conclusions: The study underlines the possibility of ZINC000008214766 acting as a potential lead compound in inhibiting Pks13-TE and presents a new therapeutic strategy against TB. These results also highlight the use of a computational workflow in drug discovery and give cause for belief that natural compounds can win the battle against resistant TB. Further in vitro and in vivo studies are warranted to validate these findings.